Low anaesthetic waste gas concentrations in postanaesthesia care unit: A prospective observational study. Issue 7 (July 2018) - Heiderich, Sebastian; Thoben, Christian; Dennhardt, Nils; Koppert, Wolfgang; Krauß, Terence; Sümpelmann, Robert; Zimmermann, Stefan; Klingler, Werner
Abstract : BACKGROUND: Volatile anaesthetics are a potential hazard during occupational exposure, pregnancy or in individuals with existing disposition to malignant hyperthermia. Anaesthetic waste gas concentration in postanaesthesia care units (PACU) has rarely been investigated. OBJECTIVE(S): The current study aims to assess concentrations of volatile anaesthetics in relation to room size, number of patients and ventilator settings in different PACUs. DESIGN: A prospective observational study. SETTING: Two different PACUs of the Hannover Medical School (Hannover, Germany) were evaluated in this study. The rooms differed in dimensions, patient numbers and room ventilation settings. PATIENTS: During the observation period, sevoflurane anaesthesia was performed in 65 of 140 patients monitored in postanaesthesia unit one and in 42 of 70 patients monitored in postanaesthesia unit two. MAIN OUTCOME MEASURES: Absolute trace gas room concentrations of sevoflurane measured with a compact, closed gas loop high-resolution ion mobility spectrometer. RESULTS: Traces of sevoflurane could be detected in 805 out of 970 samples. Maximum concentrations were 0.96 ± 0.20 ppm in postanaesthesia unit one, 0.82 ± 0.07 ppm in postanaesthesia unit two. Median concentration was 0.12 (0.34) ppm in postanaesthesia unit one and 0.11 (0.28) ppm in postanaesthesia unit two. CONCLUSION: Low trace amounts of sevoflurane were detected in both PACUs equipped with controlled air exchange systems. Occupational exposure limits were not exceeded.